Role and efficacy of denosumab in osteoporotic patients undergoing joint replacement surgery - Kakkar, Rohil Singh; Pareek, Ananya; Sharma, Tarun; Hegde, Rajendra (International Surgery Journal, 2025)
Osteoporosis is a prevalent skeletal disorder characterized by decreased bone mass and structural deterioration, significantly increasing the risk of fractures. In joint replacement surgeries, compromised bone quality in osteoporotic patients poses substantial challenges, including an elevated risk of periprosthetic fractures and implant instability. Denosumab, a monoclonal antibody targeting receptor activator of nuclear factor-kappa B ligand (RANKL), has emerged as a potent antiresorptive agent with the potential to enhance surgical outcomes in these patients. This study systematically reviews and evaluates the role and efficacy of denosumab in improving bone mineral density (BMD), minimizing periprosthetic bone loss (PBL), and enhancing implant stability in osteoporotic patients undergoing joint replacement surgery. A comprehensive literature search was conducted utilizing PubMed, MEDLINE, and Cochrane Library databases, including randomized controlled trials (RCTs) and cohort studies evaluating the impact of denosumab on BMD, PBL, and implant stability in osteoporotic patients undergoing joint replacement. Six major RCTs were included in the analysis, consistently demonstrating that denosumab enhances BMD, reduces PBL, and improves implant stability. These findings suggest that denosumab is an effective therapeutic option for optimizing surgical outcomes in osteoporotic patients undergoing joint replacement, supporting its integration into perioperative management strategies.